Mapping Groundwater-Potential Zones Using Geospatial and Decision-Making Approaches: Case Study of Ghiss-Nekkour Watershed in Northeastern Morocco - Mazzourh, Abdessamad; Taher, Morad; Ouhadi, Abdellah; Dakak, Houria; Cherkaoui Dekkaki, Hinde (Geomatics and Environmental Engineering, 2024)
Accelerated population growth has led to a heightened demand for water resources, resulting in a notable decline in underground water storage – especially in coastal areas. To effectively manage this crucial resource, the objective of this research work is to identify potential groundwater recharge areas in the Ghiss-Nekkour watershed using Saaty’s multi-criteria analysis combined with GIS and remote-sensing techniques. Initially, this work involved gathering spatial information that was related to the various parameters that govern recharge and express it in thematic maps: slope, altitude, geology, rainfall, soil, land cover, and drainage density. A reclassification was made according to their degrees of involvement in the recharge process by Saaty’s analytical hierarchy process (AHP); this was followed by a weighting of these parameters. These were subsequently integrated into a GIS in order to establish a map of potential groundwater recharge zones in the Ghiss-Nekkour watershed. The groundwater-potential map resulted in five classes: – good (165 km2) and excellent (0.9 km2) aquifer recharge potentials – situated in north and southwest portions of study area; – moderate (617 km2) aquifer recharge potentials – located in western and southern parts of watershed; – fair (551 km2) and poor (44 km2) aquifer recharge potentials – located in central zone and southeastern part of Ghiss-Nekkour watershed. Field surveys that were conducted in November 2022 and October 2023 validated the obtained results.